2019
DOI: 10.1159/000504192
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Nasal Nitric Oxide Concentrations in Preschool Children with Nasal Inflammatory Disease

Abstract: <b><i>Background:</i></b> Allergic rhinitis is an allergic inflammation of the nasal airways, and chronic rhinosinusitis is an inflammation of the paranasal sinuses. It can be induced by infection, allergy, or autoimmune problems. Diagnosis of these two diseases is made primarily based on clinical symptoms, allergen test, and imaging. The allergen test is invasive and expensive. The imaging test is harmful to children. Measurement of nasal nitric oxide (NNO) was noninvasive, without rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…11 Analyzing the data found in this review, a different cell infiltrate was observed in allergic children, markedly with mastocytosis and eosinophilia, considering the fact that the predominance of these cells increases with age and it is still necessary to determine the validity of nasal cytology in rhinitis with perennial symptoms. [8][9][10][11][12] Chen et al 19 reported that nasal nitric oxide had higher rates in children with rhinitis compared to controls. Nasal nitric oxide can function as a non-invasive tool to detect nasal inflammatory diseases, however, despite recommendations for its use, cut-off values are not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Analyzing the data found in this review, a different cell infiltrate was observed in allergic children, markedly with mastocytosis and eosinophilia, considering the fact that the predominance of these cells increases with age and it is still necessary to determine the validity of nasal cytology in rhinitis with perennial symptoms. [8][9][10][11][12] Chen et al 19 reported that nasal nitric oxide had higher rates in children with rhinitis compared to controls. Nasal nitric oxide can function as a non-invasive tool to detect nasal inflammatory diseases, however, despite recommendations for its use, cut-off values are not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on nasal nitric oxide in healthy people, particularly young children and there are concerns about cost and availability. 19,25,26 Leukotrienes are arachidonic acid metabolites whose synthesis can be stimulated by the presence of antigens and cytokines. They have an established role in inflammatory diseases, including asthma and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used this method to compare nNO levels between patients with allergic rhinitis and healthy controls. They found that, in children with allergic rhinitis, nNO levels were significantly higher than those of healthy control children (9,16,22). Based on this result, we sought to determine whether there was a direct association between nNO and EOS or total IgE levels.…”
Section: The Measurement Of No Concentrations During Expirationmentioning
confidence: 98%
“…A visual analog scale can be used to effectively assess the symptom severity (8); however, some study point out that allergen test is invasive and may incite fear in children. Further, the high cost and long inspection time increase the burden of these tests (9). Moreover, allergic rhinitis can be difficult to distinguish from other common diseases among young children (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have already outlined the relevance of nFeNO as a marker of AR inflammation in children. [15][16][17] Notably, they have shown that nFeNO level in AR (with or without asthma) was significantly increased than controls. 18,19 However, to date, no studies have been conducted in children with allergic diseases analyzing inflammatory and functional parameters together.…”
Section: Introductionmentioning
confidence: 98%